Polish adaptation of three self-report measures of job stressors: the Interpersonal Conflict at Work Scale, the Quantitative Workload Inventory and the Organizational Constraints Scale. Issue 1 (2nd January 2016) - Baka, Łukasz; Bazińska, Róża
Abstract : Aim . The objective of the present study was to test the psychometric properties, reliability and validity of three job stressor measures, namely, the Interpersonal Conflict at Work Scale, the Organizational Constraints Scale and the Quantitative Workload Inventory. Method . The study was conducted on two samples ( N = 382 and 3368) representing a wide range of occupations. The estimation of internal consistency with Cronbach's α and the test–retest method as well as both exploratory and confirmatory factor analyses were the main statistical methods. Results . The internal consistency of the scales proved satisfactory, ranging from 0.80 to 0.90 for Cronbach's α test and from 0.72 to 0.86 for the test–retest method. The one-dimensional structure of the three measurements was confirmed. The three scales have acceptable fit to the data. The one-factor structures and other psychometric properties of the Polish version of the scales seem to be similar to those found in the US version of the scales. It was also proved that the three job stressors are positively related to all the job strain measures. Conclusions . The Polish versions of the three analysed scales can be used to measure the job stressors in Polish conditions.